UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 106788 PURWODADI KECAMATAN SUNGGAL KABUPATEN DELI SERDANG TAHUN PEMBELAJARAN 2018/2019 - TAMPUBOLON, KARLOF (Unversitas Katolik Santo Thomas, 2019)
This study aims to increase student learning outcomes on mathematics subjects in the material measuring angles with standard units by applying the Problem Based Learning learning model at SDN 106788 PURWODADI, Sunggal District, Deli Serdang Regency. This type of research is Classroom Action Research. The subjects of this study were students of class IV-B, which amounted to 29 students consisting of 11 male students and 18 female students. This research was conducted in two cycles. Data from the results of this study were obtained from tests of student learning outcomes and observations.Based on the results of the study, it was shown that there was an increase in the learning outcomes of material students measuring angles with simple aircraft standard units by applying the Problem Based Learning learning model. This can be seen from improving student learning outcomes every cycle. In the pre-test of student learning outcomes carried out before the application of learning there were 4 students (32%) completed learning while 17 students (68%) had not yet finished with a grade point average of 50.93. In cycle 1 completeness of student learning outcomes there were 17 students (72%) completed in 8 students (28%) not yet completed with an average value of 70.4. The results of teacher observation amounted to 67.27% with a good category while the observations of students amounted to 64% with sufficient categories. Student learning outcomes have increased to 23 students (92%) completed 2 students (8%) have not been completed while the average value of 86.4. Teacher observation results have increased by 92.72% with very good categories while student observations amounted to 92% with very good categories. By looking at the percentage of learning outcomes and observations it can be concluded that the Application of Problem Based Learning Learning Models can improve student learning outcomes.